THE CATEGORY OF PLURALITY IN RUSSIAN AND ENGLISH LANGUAGES - Seytniyazova, Guljakhan; Atashova, Feruza (Educational Research in Universal Sciences, 2022)
The article analyzes one of the variants of verbal plurality in Russian and English - distributive plurality. The article differs from other descriptions in that it summarizes various points of view on the nature of distributivity and defines the invariant and variative characteristics of this phenomenon on the basis of extensive factual material; the mechanism for reproducing distributive semantics and its accompanying meanings in the compared languages is revealed.